The Process Mineralogy of Precious Metals in Laronde Flotation Products and Its Effect on Process Optimization - P. Blatter; P. -A. Bosse; J. Robitaille (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
The LaRonde ore is a Cu-Zn-Pb ore with gold (3-4 g/t) and silver (60-100 g/t). The precious metals are recovered with copper concentrate, zinc concentrate and cyanidation of zinc tails via Merrill Crowe precipitation. Subsequent to a recent mill expansion, excessive gold was reporting to zinc concentrate with a concurrent decrease in gold to copper concentrate. Owing to the higher return obtained from the metal, the mill endeavors to recover additional gold and silver to the copper concentrate and minimize the placement of precious metals to the zinc concentrate. A gold deportment study showed that the gold occurs mainly as küstelite, with a moderate amount of electrum and a minor amount of native gold. It also showed that various sulfur-based Au-and/or Ag-bearing coatings on liberated küstelite and electrum were the major mineralogical factors that caused gold and silver to report to zinc concentrate. By frequency, such coatings were observed on 70-80% of total liberated gold particles reporting to the zinc concentrate. Based on the gold deportment and the chemistry of the coatings, the collector chemistry was reviewed and a new collector was added into the circuit which resulted in a significant increase in gold and silver recovery to the copper concentrate. The information obtained from the mineralogy confirmed and guided other process optimization. In this paper, the authors will describe the process mineralogy of the LaRonde ores, and in particular, the mineralogical evidence diagnosing the problem. Reference will also be made to the rationale behind how the problem was solved, the results achieved, and future steps in optimization.